land governance in urban India: Reforms and regional Initiatives - Kundu, d. and Sharma, P. (Urban India)
Land is the most fundamental asset owned and managed by states and cities and is an important resource to generate revenues. India needs a robust system of land record management in order to optimize this resource. The land laws in the country are still archaic. Land governance system in India is conspicuous by the absence of scientific land record management. The changes in recording land details have not been commensurate with the change in the value of land or the number of land transactions. The Jawaharlal Nehru National Urban Renewal Mission (JNNURM), launched in 2005, made the first attempt to reform land governance in the country. Given this background, this paper overviews the achievement of states/cities with regard to the land related reforms under JNNURM and identifies reasons for the differential success of the reforms. The paper also highlights the areas where concerted efforts are needed for full implementation of the reforms and showcases some of the good practices in the concerned areas.- Reproduced
Keywords: Land governance, Land reforms, Urban land, Nehru National Urban Renewal Mission, NNURM, UPOR